ANALISIS PENYELESIAN SENGKETA INTERNAL LEMBAGA NEGARA (STUDI KASUS PELANTIKAN PIMPINAN DEWAN PERWAKILAN DAERAH REPUBLIK INDONESIA PERIODE 2017-2019) - Yanzah Bagas Nugraha; Dwi Andayani Budisetyowati (Jurnal Hukum Adigama, 2018)
The establishment of the Regional Representative Council of the Republic of Indonesia so called Dewan Perwakilan Daerah (DPD-RI) at least has two objectives. The first is to enhance justice for the people in the region. Secondly, to expanding and increasing the participation of local communities in national life. The process to form this state institution is done by amending the 3rd amendment of the 1945 Constitution of the Republic Indonesia. However, in doing that  amendment there was an internal conflict within the body of DPD-RI involving the old and the new leaders of this institution last year. The length of leadership tenure which was initially made 5 years was amended to became 2.5 years. The different length of leadership tenure was then canceled by the Supreme Court and it was decided to be the same as other institution such as The People’s Consultative Assembly and The House of Representative in that the leadership tenure should be in accordance with the electoral cycle of 5 years. However, although the regulation of DPD-RI has been canceled, the Supreme Court keeps sending its representative to guide the oath of position of the new DPD-RI leadership. The only regulation that has been introduced by the state was regulation toward conflict between state institutions and this conflict can merely be resolved by the Constitutional Court. Therefore, there is an urgent need for the state to seek solution to solve this problem to prevent the same thing happened to other state institution in the future.